2000
DOI: 10.1002/(sici)1098-2744(200004)27:4<280::aid-mc6>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of ?(1,3)fucosyltransferase antisense sequences impairs the proliferative and tumorigenic ability of human colon carcinoma cells

Abstract: Sialyl Lewis x and sialyl Lewis a are oncodevelopmental antigens involved in the pathogenesis of colon adenocarcinoma. Biosynthesis of these glycans is controlled by alpha(1,3/1,4)fucosyltransferases. We report the disruption of sialyl Lewis x/a biosynthesis and inhibition of colon carcinoma cell proliferation by stable transfection of antisense sequences directed at the human Lewis alpha(1,3/1,4)fucosyltransferase gene, FUT3, and the plasma alpha(1,3)fucosyltransferase gene, FUT6. COLO-205 cells expressed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…To this end, we found that ␣1,3 FT elevation was alone sufficient to complete sLe X synthesis and convert a non-E-selectin-binding PC-3 cell to a cell that binds E-selectin. Others have shown that ␣1,3 FTs are associated with progression of several solid cancers of the colon (34)(35)(36), breast (37), lung (38,39), liver (40), and pancreas (41,42). The question is whether PCa cells expressing abnormally high levels of ␣1,3 FTs enter BM at specific microvascular domains where E-selectin and SDF-1␣ are coexpressed constitutively and regulate leukocytic infiltration (9).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we found that ␣1,3 FT elevation was alone sufficient to complete sLe X synthesis and convert a non-E-selectin-binding PC-3 cell to a cell that binds E-selectin. Others have shown that ␣1,3 FTs are associated with progression of several solid cancers of the colon (34)(35)(36), breast (37), lung (38,39), liver (40), and pancreas (41,42). The question is whether PCa cells expressing abnormally high levels of ␣1,3 FTs enter BM at specific microvascular domains where E-selectin and SDF-1␣ are coexpressed constitutively and regulate leukocytic infiltration (9).…”
Section: Discussionmentioning
confidence: 99%
“…Frequent fucosylation, the final step within the glycosylation machinery, results in glycans that are involved in various cellular processes such as cell-cell recognition, adhesion and inflammation or tumor metastasis. Fucosylation is suggested to have paramount importance in the invasion and metastatic process of cancer stem cells (CSCs) (6) neoplastic cell proliferation and hepatocellular carcinoma cell growth in vitro, respectively, and reducing FUT3/6 expression suppressed colon carcinoma cell proliferation (7,8). MicroRNAs (miRNAs) comprise a class of small noncoding RNAs implicated in post-transcriptional RNA regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sLe X overexpressing tumors often exhibit increased transcription of ␣1, , and the increased expression of FUTs is linked to the metastatic ability of cancer cells (26,27). Consistent with ␣1,3-FUTs playing an important role in cancer, antisense-mediated decreases in FUTs, including FUT3, impair tumor growth (28) and limit metastasis (29).…”
mentioning
confidence: 97%